Developing an Islamic Emotional Spiritual Quotient (ESQ) Digital Module for Enhancing Leadership Competencies in Madrasah - Safaruddin, Safaruddin; Dwikurnaningsih, Yari; Mawardi, Mawardi (JURNAL AL-TANZIM, 2026)
This study aims to develop a digital training module based on Emotional Spiritual Quotient (ESQ) from an Islamic perspective to improve the leadership competency of madrasah principals and teachers, by specifically positioning teachers as future instructional leaders (emerging leaders). This study contributes to the leadership training literature by integrating Islamic ESQ values and well-being awareness into a stand-alone digital module, an aspect rarely discussed in previous leadership development models. Using the Research and Development (R&D) method, this study involved 30 field trial subjects. Data analysis was conducted using descriptive techniques, the Wilcoxon Signed-Rank test, and the N-Gain Score. The results showed that experts rated the module as valid (average score of 3.70), while practitioners rated it very practical (96.25%). The effectiveness test showed a significant increase in competency (p=0.000), with an N-Gain score of 0.57 (moderately effective). It was concluded that this flipbook-based digital module is feasible and effective in fostering holistic Islamic educational leadership. This study recommends using this module for independent learning to support the practical development of character-based leadership in madrasah.